Profil Sensitivitas Antibiotik Bakteri Penyebab Infeksi Saluran Kemih Terkait Kateter di Kota Mataram - Hijriani, Baiq Isti; Sakaroni, Rubiyatna; Wirdullutfi, Wirdullutfi (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2025)
Urinary tract infection (UTI) is defined as an infection caused by the growth of microorganisms in the urinary tract. One risk factor for urinary tract infection is catheterization. Treatment of UTI involves antibiotics. However, antibiotic resistance is currently increasing. This is a descriptive, observational study aimed at determining antibiotic sensitivity to bacteria causing catheter-associated urinary tract infections in Mataram City. The method used for sensitivity testing was Kirby-Bauer disk diffusion. The antibiotics tested were Ciprofloxacin and Sulphamethoxazole trimethoprime. This study used 60 urine samples from patients with UTI with catheterization. The results of the study after bacterial identification showed that 53.33% were gram-positive bacteria and 46.67% were gram-negative bacteria. The results of the ciprofloxacin antibiotic sensitivity test showed that the bacteria had inhibition zone diameters with resistant, intermediate, and sensitive categories of 36.67%, 46.67%, and 16.66%, respectively. The antibiotic sulphamethoxazole trimethoprime obtained bacteria with resistant, intermediate, and sensitive inhibition zone diameter categories of 5%, 23.33%, and 71.67%, respectively. From the results of this study, it can be concluded that bacteria causing catheterization-related urinary tract infections still show sensitivity to the antibiotic sulphamethoxazole trimethoprime compared to the antibiotic ciprofloxacin.